Insights into Labour History in Canada - Forsey, Eugène (Relations industrielles / Industrial Relations, 1965)
For the very early period, down to about 1860, there is very little to say, and it is almost all on purely local unions. From 1860 to 1871, the thing is still pretty simple. In 1871, however, a new chapter opens: the organization of the first central bodies. The 1880's open another chapter in Canadian history, a chapter which lasted till just after the turn of the century.